Efektivitas Pembelajaran Offline Pada Mata Kuliah Matematika Pasca Pandemi - Evi dwi krisna (UNIB Press, 2023)
[The Effectiveness of Offline Learning Post Pandemic in Mathematics Courses]. The purpose of this study was to evaluate the effectiveness of the post-pandemic offline learning model at INSTKI in mathematics courses. This research is a descriptive qualitative research, where the population is all INSTIKI students who receive mathematics courses using the post-pandemic offline learning model. There were 60 INSTIKI students as a sample of research subjects, who were selected by cluster random sampling. Full offline learning is carried out by research subjects face-to-face with lecturers in class. Questionnaires were distributed for data collection via google form media, and analyzed with descriptive statistics. Evaluation of the effectiveness of re-implementing offline learning is seen from the aspects of satisfaction and understanding of the material being taught. From the aspect of satisfaction, the return to implementation of this offline learning model had a positive impact, as seen from 81.67% answering very satisfied, 11.67% satisfied, and 5.00% feeling quite satisfied. Only 1.67% felt dissatisfied and no one felt very dissatisfied. From the aspect of understanding the material being taught, it also shows good results with the return of offline learning. 63.33% answered that it was easy, even 18.33% answered very easily, and 15.00% answered that it was quite easy to understand. Only 3.33% found it difficult, and no one answered that it was very difficult to understand the material being taught with this offline learning. So it can be concluded that the return of post-pandemic offline learning is effective,when evaluated from the aspect of satisfaction and understanding. Â